2022
DOI: 10.3390/ma15155120
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Naphthalene on Clay Minerals: A Molecular Dynamics Simulation Study

Abstract: Naphthalene, as one of the representative polycyclic aromatic hydrocarbons, widely exists in contaminated sites and is a potential threat to human health due to its high mobility in soil. The interaction between naphthalene and clay minerals is of great significance to the environmental behavior of naphthalene and the design of remediation technology. In this study, montmorillonite and kaolinite were selected as representative clay minerals. Naphthalene adsorption behavior on mineral surfaces and water-wet kao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Muscovite, mica, and montmorillonite were selected as representative 2:1 clay minerals. The basic structure and unit cell of these six minerals come from the Surface Model Database V1.5 of INTERFACE , (Figure ). A (5 × 3 × 1) supercell was created for each clay mineral surface to ensure that the box length was larger than 10 times the collision diameter of nitrogen.…”
Section: Validation Sectionmentioning
confidence: 99%
“…Muscovite, mica, and montmorillonite were selected as representative 2:1 clay minerals. The basic structure and unit cell of these six minerals come from the Surface Model Database V1.5 of INTERFACE , (Figure ). A (5 × 3 × 1) supercell was created for each clay mineral surface to ensure that the box length was larger than 10 times the collision diameter of nitrogen.…”
Section: Validation Sectionmentioning
confidence: 99%
“…In order to research the synergistic adsorption of multiple kinds of polymers on the surface of montmorillonite (Mt) substrates in an aqueous environment, MD method was used to reveal the different adsorption characteristics of cationic (chitosan), neutral (PAM), and anionic (MF) polymers on the surface of negatively charged montmorillonite substrates, providing a theoretical ground for the experimental implementation of synergistic flocculation of various polymers 64 . Chen et al 65 chose kaolinite and montmorillonite as representatives among the clay minerals and studied the adsorption behavior of naphthalene on the mineral surface and water‐wet kaolinite surface using MD simulation, revealing the interaction mechanism of naphthalene with clay minerals, which has important implications for the environmental behavior of naphthalene in soil and the design of remediation techniques. Ren et al 66 showed the true density distribution of surface water when NPAM was adsorbed with kaolinite and the horizontal mean mass density field for different amounts of NPAM on the kaolinite surface, as shown in Figure 4 66 …”
Section: Interface Interactions Of Clay Mineralsmentioning
confidence: 99%
“…In order to research the synergistic adsorption of multiple kinds of polymers on the surface of montmorillonite (Mt) substrates in an aqueous environment, MD method was used to reveal the different adsorption characteristics of cationic (chitosan), neutral (PAM), and anionic (MF) polymers on the surface of negatively charged montmorillonite substrates, providing a theoretical ground for the experimental implementation of synergistic flocculation of various polymers. 64 Chen et al 65 chose kaolinite and montmorillonite as representatives…”
Section: Interactions Between Agents and Clay/water Interfacementioning
confidence: 99%
“…Muscovite, mica, and montmorillonite are selected as representative 2:1 clay mineral s. The basic structure and unit cell of these six minerals come from the Surface Model Database V1.5 of INTERFACE [31,32] (Fig. 3a).…”
Section: Gcmc Simulationmentioning
confidence: 99%